Pengembangan Media Pembelajaran Interaktif berbasis Articulate Storyline 3 Pada Tema 8 Subtema Manusia dan Lingkungan - Safitri, Destriani; Suchyadi, Yudhie; Purnamasari, Ratih (Jurnal PGSD, 2023)
This research is Research and Development (RnD), with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model which aims to develop and determine the feasibility of Interactive Learning Media using Articulate Storyline 3 on Theme 8 sub-theme humans and the environment. The feasibility of Interactive Learning Media is proven through the results of expert validation which is then tested in a limited trial and evaluation stage through the distribution of material questions and student response questionnaires. The validation test results from media experts, language experts and material experts stated that the product was in the "very feasible" category for testing with an average percentage of 97%. Based on limited trials using Interactive Learning Media carried out on class V-B students, as many as 41 students obtained an average score of 87 with a classical KKM score achievement percentage of 90% and received a very good response with a percentage of 87.93% where students were very interested in using it. product. Thus it can be concluded that the development of Interactive Learning Media using Articulate Storyline 3 in Theme 8 Sub-theme humans and the environment is very suitable for use in the learning process. It is hoped that the research results will provide new knowledge regarding the use of interactive learning media using Articulate Storyline 3, which is effective in increasing student learning motivation which influences student learning outcomes.